Hollow high-entropy spinel oxide catalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202611012274.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-27
AI Technical Summary
上述方案分别侧重于VOCs催化氧化或甲醇重整制氢,均未涉及锂硫电池中多硫化锂吸附/转化催化
[0022]与现有实心尖晶石氧化物相比,本发明的中空结构能够提高反应界面和活性位点暴露,缓解充放电过程中的体积变化,并缩短硫物种与催化活性位点之间的传输距离。
Smart Images

Figure CN122974302A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-sulfur battery catalytic materials technology, and in particular to a hollow high-entropy spinel oxide catalyst, its preparation method, and its application. Background Technology
[0002] Lithium-sulfur batteries possess high theoretical specific capacity and energy density, making them a promising next-generation energy storage system. However, during charge and discharge, the redox kinetics of sulfur species are slow, and the intermediate product lithium polysulfides is easily dissolved and migrated, triggering a shuttle effect that leads to loss of active materials, reduced coulombic efficiency, and decreased cycle stability. Simultaneously, volume changes occur between sulfur and its discharge products, placing higher demands on electrode structure stability and interfacial mass transfer.
[0003] Introducing polar catalytic materials to adsorb lithium polysulfides and promote their conversion is an important approach to improving the performance of lithium-sulfur batteries. Spinel-type transition metal oxides, with their tunable metal cation sites and oxygen coordination structures, have potential applications in the adsorption and conversion catalysis of lithium polysulfides. However, traditional spinel oxides typically suffer from insufficient electronic structure regulation, limited exposure of active sites, long transport paths in solid particles, and difficulty in buffering volume changes, which restricts their application effectiveness.
[0004] In the prior art, CN121819861A discloses a copper-rich high-entropy spinel composite oxide catalyst for VOCs treatment, and CN121360570A discloses a supported spinel catalyst for methanol steam reforming to produce hydrogen. These solutions focus on either VOCs catalytic oxidation or methanol reforming to produce hydrogen, respectively, and neither involves the adsorption / conversion catalysis of lithium polysulfides in lithium-sulfur batteries.
[0005] Therefore, how to construct catalytic materials that combine single-phase high-entropy spinel structure and hollow morphology to improve the exposure of active sites, shorten transport paths, buffer volume changes, and promote the adsorption, nucleation, and conversion of lithium polysulfides remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide an oxide catalyst that has both a high-entropy single-phase spinel structure and a hollow morphology, which can promote the adsorption and conversion of lithium polysulfides in lithium-sulfur batteries, as well as its preparation method and application.
[0007] To achieve the above objectives, the present invention provides a hollow high-entropy spinel oxide catalyst, wherein the metal elements in the catalyst include Co, Ni, Cu, Mg and Cr, and the catalyst has a single-phase spinel oxide structure.
[0008] Preferably, the molar ratio of Co, Ni, Cu, Mg, and Cr is (0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2); more preferably, it is 1:1:1:1:1. By employing five metal elements to jointly constitute the metal cation sites of the spinel-type oxide, a high-entropy effect and lattice distortion can be introduced to regulate the local coordination environment and electronic structure of active metals such as Co and Ni, thereby improving the adsorption and conversion catalytic ability of lithium polysulfides.
[0009] Preferably, the chemical composition of the catalyst is (CoNiCuMgCr)3O4 based on the metal and oxygen elements, or it is a spinel-type oxide in which Co, Ni, Cu, Mg and Cr together constitute the metal cation sites.
[0010] Preferably, the overall sphere diameter of the hollow high-entropy spinel oxide catalyst is 0.5-5 μm, more preferably 1-3 μm. The hollow structure provides a high specific surface area and abundant reaction interfaces, increasing the exposure of catalytic active sites. The internal cavity can alleviate volume changes during the charging and discharging process of lithium-sulfur batteries and is beneficial for shortening the transport distance between sulfur species and active sites.
[0011] This invention also provides a method for preparing the above-mentioned hollow high-entropy spinel oxide catalyst, comprising the following steps:
[0012] S1. Dissolve cobalt salt, nickel salt, copper salt, magnesium salt, chromium salt and glucose in water to obtain a mixed solution of precursors;
[0013] S2. The precursor mixture solution is subjected to a hydrothermal reaction to allow the metal cations and glucose to undergo hydrothermal polymerization to form a carbon microsphere precursor containing metal elements.
[0014] S3. The carbonaceous microsphere precursor is calcined in an oxygen-containing atmosphere to obtain the hollow high-entropy spinel oxide catalyst.
[0015] Preferably, in step S1, the cobalt salt, nickel salt, copper salt, magnesium salt, and chromium salt are nitrates, acetates, or chlorides, respectively; more preferably, the cobalt salt, nickel salt, copper salt, magnesium salt, and chromium salt are cobalt nitrate, nickel nitrate, copper nitrate, magnesium nitrate, and chromium nitrate, respectively.
[0016] Preferably, in step S1, the total concentration of metal ions in the precursor mixture solution is 0.05-0.50 mol / L, more preferably 0.10-0.25 mol / L; the molar ratio of glucose to the total amount of metal ions is 1.5-5.0:1, more preferably 2.0-3.0:1. By controlling the total concentration of metal ions and the amount of glucose, the sphericity of carbon microspheres, the uniform encapsulation of multiple metal elements, and the formation of hollow structures during subsequent calcination can be balanced.
[0017] Preferably, in step S2, the hydrothermal reaction temperature is 160-200℃ and the time is 300-500 min; more preferably, the hydrothermal reaction temperature is 180℃ and the time is 400 min. During the hydrothermal process, glucose, as a carbon source and chelating agent, can form MOC bonds with metal cations and polymerize to form monodisperse amorphous carbon microspheres, so that various metal elements are uniformly dispersed in the carbon template.
[0018] Preferably, after the reaction in step S2 is completed, the obtained product is centrifuged, washed with deionized water and ethanol, and dried at low temperature to obtain carbon microsphere precursor; the centrifugation speed is 6000-10000 r / min, the centrifugation time is 3-10 min, the drying temperature is 50-80℃, and the drying time is 8-16 h.
[0019] Preferably, in step S3, the oxygen-containing atmosphere is an air atmosphere; in step S3, the temperature is increased to 450-550℃ at a heating rate of 0.5-2℃ / min and held for 0.5-2h; more preferably, the temperature is increased to 500℃ at a heating rate of 1℃ / min and held for 1h. Slow heating can establish a radial temperature gradient within the carbon microspheres, allowing the carbon microspheres to be gradually oxidized and consumed, and removing the internal carbon template during the formation of the oxide framework, thereby forming a hollow structure and simultaneously generating a single-phase high-entropy spinel-type oxide.
[0020] This invention also provides the application of the above-mentioned hollow high-entropy spinel oxide catalyst in lithium-sulfur batteries. The catalyst can be used as a cathode catalytic additive, a sulfur-supported host material, a membrane modification layer material, or a lithium polysulfide conversion catalytic material in lithium-sulfur batteries.
[0021] The beneficial effects of this invention are:
[0022] Compared with existing solid spinel oxides, the hollow structure of this invention can improve the exposure of the reaction interface and active sites, alleviate volume changes during charging and discharging, and shorten the transport distance between sulfur species and catalytic active sites.
[0023] Compared with ordinary single metals or medium-entropy oxides, this invention introduces lattice distortion and high-entropy effects through the synergistic use of five metals (Co, Ni, Cu, Mg, and Cr), which is beneficial for regulating the coordination environment and electronic structure of active metal cations and enhancing the adsorption and catalytic conversion capabilities of lithium polysulfides.
[0024] This invention employs a spatial gradient oxidation method that combines glucose hydrothermal carbon sphere templates with low-heat-rate air calcination. This method can construct hollow morphologies while forming single-phase high-entropy spinel oxides, and the process path is simple.
[0025] When the catalyst of this invention is used in lithium-sulfur batteries, it can reduce the polysulfide conversion energy barrier and improve the Li2S nucleation / deposition kinetics, thereby improving battery capacity, rate performance and cycle stability. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the reaction pathway in which sulfur species are gradually transformed from S8 to Li2S.
[0027] Figure 2 This is a SEM image of the (CoNiCuMgCr)3O4 hollow high-entropy spinel oxide catalyst prepared in Example 1; wherein, Figure 2 Image a is a low-magnification SEM image. Figure 2 b is Figure 2 The area within the dashed box in image a corresponds to a magnified view of a single hollow microsphere. Figure 2 c is a high-magnification SEM image of the shell surface. Figure 2 d is a cross-sectional SEM image of the broken hollow microspheres.
[0028] Figure 3 This is the XRD pattern of the hollow high-entropy spinel oxide catalyst prepared in Example 1.
[0029] Figure 4 This is a graph showing the free energy change of the sulfur species conversion process on the catalyst surface in Examples 1, 1, and 2 of the present invention.
[0030] Figure 5 This is the Li2S deposition test curve of the catalyst in Example 1 of this invention.
[0031] Figure 6 These are electrochemical performance test graphs of lithium-sulfur batteries corresponding to Embodiment 1, Comparative Example 1, and Comparative Example 2 of the present invention; wherein, Figure 6 a represents the cycle performance and coulombic efficiency curves at a 1C rate. Figure 6 b represents the rate performance test curve. Figure 6 The long-cycle performance and coulombic efficiency curves at a rate of 0.5C. Detailed Implementation
[0032] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Without departing from the concept of the present invention, those skilled in the art can make appropriate adjustments to the types of raw materials, the proportions of raw materials, and the process parameters.
[0033] The parameters and sources of some raw materials in the examples are as follows:
[0034] The cobalt nitrate was cobalt nitrate hexahydrate (Co(NO3)2·6H2O, analytical grade, purity ≥99.0%).
[0035] The nickel nitrate was nickel nitrate hexahydrate (Ni(NO3)2·6H2O, analytical grade, purity ≥98.5%).
[0036] Copper nitrate was copper nitrate trihydrate (Cu(NO3)2·3H2O, analytical grade, purity ≥99.0%).
[0037] Magnesium nitrate is magnesium nitrate hexahydrate (Mg(NO3)2·6H2O, analytical grade, purity ≥99.0%).
[0038] Chromium nitrate was chromium nitrate nonahydrate (Cr(NO3)3·9H2O, analytical grade, purity ≥99.0%).
[0039] The glucose is anhydrous D-glucose, analytical grade, with a purity ≥99.0%.
[0040] The above reagents can be purchased from conventional commercial channels such as Sinopharm Chemical Reagent Co., Ltd., Shanghai McLean Biochemical Technology Co., Ltd., or Shanghai Aladdin Biochemical Technology Co., Ltd.; the resistivity of deionized water is not less than 18.0 MΩ·cm.
[0041] Example 1
[0042] A method for preparing a hollow high-entropy spinel oxide catalyst includes the following steps:
[0043] S1. Weigh out 0.582 g of cobalt nitrate hexahydrate, 0.582 g of nickel nitrate hexahydrate, 0.483 g of copper nitrate trihydrate, 0.513 g of magnesium nitrate hexahydrate, and 0.800 g of chromium nitrate nonahydrate according to the molar ratio of Co:Ni:Cu:Mg:Cr of 1:1:1:1:1. Add them to 60 mL of deionized water and stir to dissolve. Then add 4.50 g of anhydrous D-glucose and continue stirring for 30 min to obtain a homogeneous precursor mixture solution. The amount of each metal element is 2.00 mmol, the total amount of metal ions is 10.0 mmol, the total concentration of metal ions is 0.167 mol / L, and the molar ratio of glucose to total metal ions is 2.5:1.
[0044] S2. The precursor mixture obtained in step S1 was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, sealed, and hydrothermally treated at 180 °C for 400 min, then naturally cooled to room temperature. During the reaction, the metal cations chelated with glucose and formed MOC bonds, and the glucose hydrothermally polymerized to produce monodisperse amorphous carbon microspheres. After the reaction, the product was centrifuged at 8000 r / min for 5 min to collect the precipitate, washed three times each with deionized water and anhydrous ethanol, and then vacuum dried at 60 °C for 12 h to obtain carbon microsphere precursors containing Co, Ni, Cu, Mg and Cr.
[0045] S3. The carbonaceous microsphere precursor obtained in step S2 is spread in an alumina ceramic boat and placed in a muffle furnace. The temperature is increased to 500℃ in an air atmosphere at a heating rate of 1℃ / min and held for 1h. The air flow rate is 100mL / min. After the holding period, the temperature is cooled to room temperature with the furnace and ground through a 200-mesh sieve to obtain the (CoNiCuMgCr)3O4 hollow high-entropy spinel oxide catalyst.
[0046] The catalyst has a hollow structure, with an overall sphere diameter of approximately 2 μm.
[0047] Comparative Example 1
[0048] A method for preparing a common ternary medium-entropy oxide catalyst is basically the same as that in Example 1, except that: in step S1, only cobalt salt, nickel salt and copper salt are used as metal sources. 0.970 g of cobalt nitrate hexahydrate, 0.969 g of nickel nitrate hexahydrate and 0.805 g of copper nitrate trihydrate are weighed according to the molar ratio of Co:Ni:Cu of 1:1:1. The amount of each metal element is 3.33 mmol, and the total amount of metal ions is still 10.0 mmol. The amount of glucose, the amount of deionized water, the hydrothermal conditions, the centrifugal washing and drying conditions and the calcination conditions are the same as in Example 1, and the (CoNiCu)3O4 oxide catalyst is obtained.
[0049] Comparative Example 2
[0050] A method for preparing a single-metal spinel oxide catalyst is basically the same as that in Example 1, except that: in step S1, only cobalt salt is used as the metal source, 2.910 g of cobalt nitrate hexahydrate is weighed, the amount of Co element is 10.0 mmol, and the total amount of metal ions is the same as in Example 1; the amount of glucose, the amount of deionized water, the hydrothermal conditions, the centrifugal washing and drying conditions, and the calcination conditions are all the same as in Example 1, and Co3O4 catalyst is obtained.
[0051] Test Example 1: Structural and Morphological Characterization
[0052] The elemental surface distribution of the (CoNiCuMgCr)3O4 hollow high-entropy spinel oxide catalyst prepared in Example 1 was characterized by XRD, SEM and EDS.
[0053] XRD testing is used to confirm whether the catalyst forms a single-phase spinel oxide structure; SEM testing is used to observe the overall microsphere morphology of the catalyst; EDS elemental surface distribution testing is used to confirm the co-distribution state of Co, Ni, Cu, Mg and Cr in the shell.
[0054] Test results show that the catalyst prepared in Example 1 is a high-entropy spinel-type oxide with a hollow structure and an overall sphere diameter of approximately 2 μm. This structure improves the exposure of active sites and provides a buffer space for volume changes during the charging and discharging process of lithium-sulfur batteries.
[0055] XRD testing was performed using Cu Kα rays with a tube voltage of 40 kV, a tube current of 40 mA, a scanning range of 10°–80°, a step size of 0.02°, and a scanning rate of 5° / min.
[0056] SEM testing was performed using a field emission scanning electron microscope. Before testing, the sample powder was uniformly dispersed on the surface of the conductive adhesive and sputtered with gold for 60 seconds.
[0057] If necessary, EDS elemental distribution tests can be used to confirm the uniform distribution of Co, Ni, Cu, Mg, and Cr in the microspheres.
[0058] Test Example 2: Calculation of Lithium Polysulfide Adsorption and Conversion
[0059] Density functional theory was used to calculate the adsorption energy of Li2S4 in Example 1, Comparative Example 1 and Comparative Example 2, and the Gibbs free energy change during the sulfur species transformation process was also calculated.
[0060] Calculations were performed using the VASP software package, employing the PAW pseudopotential and the generalized gradient approximation exchange-correlated functional in PBE form, and correcting for van der Waals interactions using the DFT-D3 method. A surface model was constructed using the low-index crystal planes of spinel oxide, with a vacuum layer thickness of 15 Å; the plane wave cutoff energy was 500 eV, the k-point grid was 3×3×1, the electronic energy convergence standard was 1.0×10⁻⁵ eV, and the atomic force convergence standard was 0.02 eV / Å. The Li₂S₄ adsorption energy was calculated as Eads = E(substrate + Li₂S₄) - E(substrate) - E(Li₂S₄), where E(substrate + Li₂S₄) is the total energy after adsorption, E(substrate) is the energy of the catalyst surface model, and E(Li₂S₄) is the energy of the isolated Li₂S₄ molecule. The Gibbs free energy change was calculated as ΔG = ΔE + ΔZPE - TΔS, with a temperature of 298.15 K. The reaction pathway for the gradual transformation of sulfur species from S8 to Li2S8, Li2S6, Li2S4, and Li2S2 to Li2S is as follows: Figure 1 As shown.
[0061] Calculation results show that the adsorption energies of Li₂S₄ for Example 1, Comparative Example 1, and Comparative Example 2 are -2.59 eV, -2.06 eV, and -1.64 eV, respectively. Example 1 exhibits a more negative adsorption energy for Li₂S₄, indicating a stronger adsorption effect; Comparative Example 1 shows the second strongest adsorption effect, while Comparative Example 2 shows a relatively weaker adsorption effect. These results demonstrate that the high-entropy spinel structure composed of five metal elements—Co, Ni, Cu, Mg, and Cr—can regulate the local coordination environment and electronic structure of the surface active sites, thereby enhancing the adsorption of lithium polysulfides.
[0062] Depend on Figure 4 It can be seen that during the gradual conversion of S8 to Li2S via Li2S8, Li2S6, Li2S4, and Li2S2, the free energy change in the rate-limiting step of Example 1 is 0.68 eV, which is lower than 0.91 eV in Comparative Example 1 and 1.08 eV in Comparative Example 2. This indicates that Example 1 can reduce the reaction energy barrier in the conversion of lithium polysulfides to Li2S and promote the conversion reaction of sulfur species. This result shows that the five-element high-entropy spinel structure of Co, Ni, Cu, Mg, and Cr has superior catalytic ability for the conversion of lithium polysulfides.
[0063] Test Example 3: Li2S Deposition Test
[0064] The catalytic effects of Example 1, Comparative Example 1, and Comparative Example 2 on Li2S nucleation and deposition were evaluated using Li2S deposition tests.
[0065] The specific method is as follows: The catalysts obtained in Example 1, Comparative Example 1, and Comparative Example 2 were mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 7:2:1, respectively. N-methylpyrrolidone was used as a solvent to prepare a slurry, which was then coated onto the surface of carbon paper. After drying, the slurry was cut into working electrodes with a catalyst loading of 0.20 mg / cm³. 2 A CR2032 coin cell was assembled using lithium foil as the counter electrode and reference electrode, and Celgard 2400 membrane as the separator.
[0066] The Li₂S deposition test used a tetraethylene glycol dimethyl ether solution containing 0.20 mol / L Li₂S₈ as the electrolyte on the positive electrode side, and a mixed solution of 1.0 mol / L LiTFSI and 1.0 wt% LiNO₃ in DOL / DME (volume ratio of DOL to DME was 1:1) on the negative electrode side. Before testing, the battery was discharged at a constant current to 2.06 V to reduce higher-order lithium polysulfides to lower-order lithium polysulfides. Subsequently, Li₂S deposition was tested under a constant potential of 2.05 V, and the current-time curve was recorded. The Li₂S deposition capacity was calculated by integrating the current-time curve during the constant potential phase and converted based on the sulfur mass.
[0067] The Li2S deposition test curve of Example 1 is as follows: Figure 5 As shown, the test results of Comparative Examples 1 and 2 are compared with those of Example 1, and the statistical results are shown in Table 5.
[0068] Test results are as follows Figure 5 As shown in Table 5.
[0069] Table 5. Li2S deposition test results for different catalysts
[0070]
[0071] Depend on Figure 5 As shown in Table 5, Example 1 exhibits a shorter Li₂S nucleation time and a higher peak current, with a nucleation time of approximately 530 s, a peak current of approximately 1.75 mA, and a Li₂S deposition capacity of 504.32 mAh / g. In contrast, Comparative Examples 1 and 2 have nucleation times of 660 s and 820 s, respectively, peak currents of 1.28 mA and 0.92 mA, and Li₂S deposition capacities of 378.72 mAh / g and 286.45 mAh / g, respectively.
[0072] The above results show that the pentagonal high-entropy spinel structure of Example 1 can provide more synergistic catalytic sites, and the hollow structure can provide internal cavities and a larger reaction interface, which is beneficial to shorten the mass transfer distance between lithium polysulfides and catalytic active sites, thereby promoting the nucleation and deposition of lithium polysulfides to Li2S and improving the Li2S deposition kinetics.
[0073] Test Example 4: Lithium-sulfur battery performance test
[0074] The (CoNiCuMgCr)3O4 hollow high-entropy spinel oxide catalyst prepared in Example 1 was used in a lithium-sulfur battery, and its rate performance and cycle performance were tested.
[0075] The lithium-sulfur battery was assembled using CR2032 coin cells. Sublimed sulfur and the catalyst from Example 1 were mixed at a mass ratio of 7:3 and heated in a sealed environment at 155°C for 12 hours to obtain a sulfur / catalyst composite material. The sulfur / catalyst composite material, Super P conductive carbon black, and PVDF were then dispersed in N-methylpyrrolidone at a mass ratio of 8:1:1 to prepare a positive electrode slurry. This slurry was coated onto carbon-coated aluminum foil, vacuum dried at 60°C for 12 hours, and then cut into sheets, controlling the sulfur surface loading to be 3.0 ± 0.2 mg / cm³. 2The electrolyte was a mixed solvent of 1.0 mol / L LiTFSI and 0.2 mol / L LiNO3 dissolved in a DOL / DME ratio of 1:1 (volume ratio), with an electrolyte / sulfur ratio of 8 μL / mg. The separator was a Celgard 2400 polypropylene membrane. The negative electrode was a lithium metal sheet with a diameter of 15.6 mm and a thickness of approximately 450 μm. The charge / discharge voltage window was 1.7–2.8 V, the test temperature was 25 ± 2 °C, and the rate calculation was based on 1C = 1675 mA / g (based on sulfur mass).
[0076] With a sulfur surface loading of 3 mg / cm³ 2 Under the condition of 0.1C rate, the lithium-sulfur battery containing the catalyst of Example 1 achieved a discharge specific capacity of 1632.3 mAh / g in the first cycle; it still maintained a discharge specific capacity of 873.8 mAh / g at a high current density of 3.0C; and after 500 cycles at 0.5C, the coulombic efficiency was maintained at 98.6%.
[0077] Depend on Figure 6 As can be seen from a, at a 1C rate and a sulfur surface loading of approximately 3.0 mg / cm³, 2 Under the condition of an electrolyte / sulfur ratio of 8 μL / mg, the battery corresponding to Example 1 maintains a high discharge specific capacity during cycling, and the coulombic efficiency is close to 100%, which is significantly better than Comparative Example 1 and Comparative Example 2, indicating that Example 1 can improve the cycle stability of lithium-sulfur batteries.
[0078] Depend on Figure 6 As shown in b, as the rate gradually increases from 0.1C to 3C, the battery corresponding to Example 1 maintains a high discharge specific capacity at each rate; when the rate is restored from 3C to 1C, the capacity can be significantly restored, indicating that the catalyst of Example 1 has good rate performance and reaction kinetics.
[0079] Depend on Figure 6 c indicates that at a 0.5C rate, the sulfur surface loading is approximately 4.0 mg / cm³. 2 Under the condition of an electrolyte / sulfur ratio of 8 μL / mg, the battery corresponding to Example 1 still maintains a high discharge specific capacity and a coulombic efficiency close to 100% during 500 cycles, indicating that the catalyst of the present invention still has good stability under high sulfur surface loading and long cycling conditions.
[0080] The above results indicate that the hollow high-entropy spinel oxide catalyst of this invention can improve the sulfur species conversion kinetics in lithium-sulfur batteries, suppress the shuttle effect, and enhance the capacity, rate performance, and cycle stability of lithium-sulfur batteries.
[0081] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A hollow high-entropy spinel oxide catalyst, characterized in that: The catalyst contains the metal elements Co, Ni, Cu, Mg and Cr, and has a single-phase spinel oxide structure; the molar ratio of Co, Ni, Cu, Mg and Cr is (0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2).
2. The hollow high-entropy spinel oxide catalyst as described in claim 1, characterized in that: The molar ratio of Co, Ni, Cu, Mg and Cr is 1:1:1:1:1; and / or the chemical composition of the catalyst, calculated based on the metal and oxygen elements, is (CoNiCuMgCr)3O4, or a spinel-type oxide in which Co, Ni, Cu, Mg and Cr together constitute metal cation sites.
3. The hollow high-entropy spinel oxide catalyst as described in claim 1 or 2, characterized in that: The overall sphere diameter of the hollow high-entropy spinel oxide catalyst is 0.5-5 μm.
4. A method for preparing a hollow high-entropy spinel oxide catalyst as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. Dissolve cobalt salt, nickel salt, copper salt, magnesium salt, chromium salt and glucose in water to obtain a mixed solution of precursors; The total concentration of metal ions in the precursor mixture solution is 0.05-0.50 mol / L, and the molar ratio of glucose to total metal ions is 1.5-5.0:
1. S2. The precursor mixture solution is subjected to a hydrothermal reaction to allow the metal cations and glucose to undergo hydrothermal polymerization to form a carbon microsphere precursor containing metal elements. S3. The carbon microsphere precursor is calcined in air to obtain the hollow high-entropy spinel oxide catalyst. In step S3, the temperature is increased to 450-550℃ at a heating rate of 0.5-2℃ / min and held at that temperature for 0.5-2h.
5. The method for preparing the hollow high-entropy spinel oxide catalyst as described in claim 4, characterized in that: In step S1, the cobalt salt, nickel salt, copper salt, magnesium salt, and chromium salt are respectively nitrate, acetate, or chloride.
6. The method for preparing the hollow high-entropy spinel oxide catalyst as described in claim 4, characterized in that: In step S2, the temperature of the hydrothermal reaction is 160-200℃ and the time is 300-500 min.
7. The application of the hollow high-entropy spinel oxide catalyst as described in any one of claims 1-3 in lithium-sulfur batteries.
8. The application as described in claim 7, characterized in that: The hollow high-entropy spinel oxide catalyst is used as a positive electrode catalytic additive for lithium-sulfur batteries, a sulfur-supported host material, a membrane modification layer material, or a lithium polysulfide conversion catalytic material.
9. A lithium-sulfur battery, characterized in that: Including the hollow high-entropy spinel oxide catalyst according to any one of claims 1-3.